The Importance Of Protecting The Personal Data Of Social Media Users In The Era Of Digitalization - Mohammad Gufran Katili (Universitas Negeri Gorontalo, 2019)
Abstract: Technology that moves forward and develops over time makes various kinds of changes happening around us. Social media was born as a form of technological sophistication itself that brings convenience to its users. This study uses normative methods by analyzing forms of legal protection in the context of personal data contained in several related laws. It is hoped that this article can be a characteristic of the knowledge of its readers in building a common awareness of the importance of protecting each other's data from crimes that may lurk. The results obtained through this study through various existing laws related to the form of personal data protection itself are not spelled out explicitly, causing legal blurring that leads to less effective enforcement of existing laws as a form of personal data protection.Keywords: Technology; Personal data; Social media.